Traditional Marketing Mix as a Tools to Improve Consumer Buying Decision - Tandar, Edric (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
Everyone knows that living in this world we as a human individual have needs. According to (Grawe,2007, p.169) “The goal a person forms during his or her life ultimately serve the satisfaction of basic needs”. Currently in Indonesia, there are many companies and business that allows people to earn money. One of the various industries that produces a lot of earnings is the food and beverage service industry. Food and beverage services can be defined as the process of preparing and serving food and beverage to the customers. Additionally, currently a particular F&B service is on the rise in Indonesia, Coffeeshops, the number of coffeeshops in Indonesia has kept on growing and it can notably be seen by looking at various coffeeshops located everywhere in the past few years. A coffeeshop named Yakun Kaya Toast however, does belong to the coffeeshop industry but does not “really” belong in this category. Yakun Kaya Toast’s history was that in the year 1926 a young boy named Loi Ah Koon set sail from Hainan Island to Singapore, knowing nobody there he naturally joined a Hainanese community there he then was introduced to work as an assistant in a Hainanese coffee stall. This study aims to analyze how marketing mix can help customer purchasing decision in , the Yakun Kaya Toast located in Jl. Iskandar Muda No.109, Sei Sikambing D, Kec. Medan Petisah, Kota Medan, Sumatera Utara 20111.The sample used in this study is 110 respondents. For processing and analyzing data in this study, namely by using AMOS version 22.0 as software for data processing. This study has four hypotheses and all of them have significant results